Investigation of the Removal of ASH, Sulphur and Other Contaminants From Coal by Wet Magnetic Separation. (1995) - Karmazin, V. I.; Mostika, Yu. S.; Savluk, E. N.
Abstract : This paper presents the results of wet magnetic beneficiation of finely ground coals by high–gradient magnetic separation, with the aim to remove deleterious and toxic impurities.